Resíduos sólidos de serviços de saúde : diagnóstico e diretrizes para gestão hospitalar - Tramontini, Atilio Cesar Bonotto (2009)
The existence of a great number of recommendations, norms and legislations in the worldwide scope regarding the Waste of Health Services (WHS), which steem for a better system and final destination, as it is a theme which influences occupational health interests, public health and the environment, has been observed. In force in Brazil, there are the norms RDC n° 306/04 of ANVISA and the Resolution n° 358/05 of Conama, that are guidelines for the elaboration of the Waste Management Plan WMPHS. The present work is comprised of a diagnoses of the hospital waste created in 5 Hospitals located in the town of Passo Fundo-RS and a reference Hospital in Porto Alegre, in the light of the current Brazilian legislation. This diagnoses, together with the norms in force, has been used as subsides to the elaboration of the structure of the WMPHS. In order to reach the objective of this work, the methodological conception, the data survey and the information systematization are presented in this work. The data collection has been accomplished by means of interviews, systematized observation, WMPHS analysis by considering the aspects related to generation, segregation, packing, collection, storage, transportation, treatment and final destination, as well as public health preservation measures and also by the characterization of the waste created. Through the interviews and observations systematized it was possible to examine that the hospitals studied do not have a management system of RSS in accordance with the current Brasilian legislation. Through the study, it has been concluded the necessity of adaptation of five hospitals researched in accordance with the current legisltations, emphasizing the implantation of a WMPHS, besides an continuing education program in service